SYNTHESIS AND CHARACTERIZATION OF HDPE PLASTIC FILM FOR HERBICIDE CONTAINER USING FLY ASH CLASS F AS FILLER - Yatim Lailun Ni’mah; Lukman Atmaja; Hendro Juwono (Indonesian Journal of Chemistry, 2009)
High Density Polyethylene (HDPE) plastic plays an important role in various applications, for example, it can be used as a container (bottle). Petrokimia Kayaku Company, a branch of Petrokimia Company of Gresik, produces herbicides using HDPE plastic bottles as their container. Those plastic bottles undergo degradation (kempot) for certain period of time. The aim of this research is to characterize and to synthesize the HDPE plastic film with class F fly ash as filler. The results expected from this research are producing the plastic with a better properties and durability. This research was initiated by taking the sample of HDPE plastic bottle and herbicides (containing Gramakuat, on active material parakuat dichloride) at Petrokimia Kayaku Company. Both the initial HDPE and the degraded bottles was analyzed their tensile strength and Fourier Transform-Infra Red (FTIR) spectral. The next step was to synthesize the HDPE plastic film using class F fly ash as filler and a coupling agent. The filler concentrations were 0%, 5%, 10%, 15%, and 20wt %. The best result was 5% filler concentration with tensile strength of 27.7 lbs. This HDPE film was then subjected to degradation test using pyridine solution with various concentrations (1%, 3% and 5%) for two weeks, thermal degradation at 100 °C for two weeks and chemical resistance by xylene with soak time variation of 24 h, 98 h and 168 h. The result of degradations test show that the value of tensile strength was decreased with the increase of filler consentration. The chemical resistance, however, was increased.